Relations of left atrial appendage emptying flow velocity to left atrial appendage thrombus in Mitral Stenosis Patients by transesophageal echocardiography examination - Debby Kurniawan (ARKAVI [Arsip Kardiovaskular Indonesia), 2019)
Left atrial appandage emptying flow velocity is a measurement of the velocity of blood flow in left atrial appendage with pullsed doppler echocardiography modality, This examination were done in order for evaluate the clots which caused by mitral stenosis. Descriptive method in patients with mitral stenosis using 14 patients as the subject of this study. There is 14 patients who meet the criteria in the study, in this study the results obtained Left atrial appendage emptying velocity to left atrial appendage thrombus has no significant relation. There is no correlation with each other. Due to the value of a distant ratio. Keywords: Left atrial appendage emptying velocity, left atrial appendage, Mitral Stenosis. Left atrial appendage emptying velocity merupakan teknik pengukuran kecepatan aliran darah di left atrial appendage dengan modalitas pullsed doppler echocardiography, pemeriksaan ini dilakukan untuk mengevaluasi pembekuan darah yang di sebabkan oleh mitral stenosis. Metode dekriktif pada pasien Mitral Stenosis dengan menggunakan 14 pasien sebagai subjek penelitian. Didapat sampel penelitian sebanyak 14 pasien yang memenuhi kriteria pada penelitian. Pada penelitian ini hasil uji korelasi Left atrial appendage emptying velocity terhadap left atrial appendage thrombus Tidak bermakna. Pada penelitian ini tidak ada korelasi antara variabel Left atrial appendage emptying velocity dengan left atrial appendage thrombus. Dikarenakan nilai rasio yang jauh. Kata Kunci: Left atrial appendage emptying velocity, left atrial appendage, Mitral Stenosis.